Capability and Maturity Analysis of an Academic Final Project Information System Using COBIT - Agung Surya Putra; Luthfi Indana (bit-Tech, 2026)
The implementation of the Final Project Information System (SISTA) plays a critical role in supporting academic processes in higher education; however, inadequate information technology governance can lead to operational instability and service quality issues. This study addresses the limited application of the COBIT 2019 framework in evaluating academic information systems within Indonesian universities by assessing the capability level, maturity level, and governance gaps of SISTA at Universitas Merdeka Malang. A quantitative approach was employed, utilizing questionnaires, interviews, and documentation analysis to measure current and target capability levels across four COBIT 2019 domains: Align, Plan, and Organize (APO); Build, Acquire, and Implement (BAI); Deliver, Service, and Support (DSS); and Monitor, Evaluate, and Assess (MEA). The results show that most governance processes have achieved capability level 3 (Established), indicating consistent and standardized implementation, while the overall maturity level ranges from Defined to Managed. Gap analysis reveals that the DSS domain exhibits the largest discrepancy, particularly affecting operational stability and problem management, whereas the APO and MEA domains demonstrate relatively smaller gaps. These findings highlight critical governance weaknesses that directly impact system reliability and user experience. The study provides actionable insights for prioritizing governance improvements and offers a practical reference for higher education institutions seeking to strengthen sustainable IT governance through the COBIT 2019 framework.